Investigating the Work Attitude Differences of Younger Generations in North Cyprus Hospitality Industry - Akhshik, Arash (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
This study mainly focuses on the differences between the younger generations, generation Y which was born between 1985 – 1994 and generation Z cohort which was born after 1995 on their attitudes towards work. Different constructs of work attitudes has been measured and the results reveal the significant differences in work attitude of younger generations. There are significant differences in all constructs of work attitude, except for training and development perception, further excavation of these differences reveals valuable results, which human resource managers are trying to maximize in their organizations. Generation Z, has rated significantly lower than their previous generation on job satisfaction, perceived employability engagement, organizational citizenship behavior, perceived fairness, perception of rewards and recognition, perceived job security. The youngest generation is less committed to their organizations and has high intentions to quit and switch jobs compared to their previous generation, despite their high perception of organizational and supervisory supports. Keywords: Generation Z, Generation Y, Generational Differences, Work related Attitude, Tourism Industry, HRM

ÖZ : Bu çalışma, genel olarak 1985-1994 arası doğumlulardan oluşan Y nesli ile 1995 ve sonrası doğumluları kapsayan Z neslinin iş hayatındaki davranış farklılıklarına odaklanmıştır. İş yaşamındaki farklı yapılar ölçülmüş ve sonuçların yeni neslin iş hayatında anlamlı farklılıklar gösterdiği sonucuna varılmıştır. Eğitim ile gelişimin algılanması dışında iş hayatındaki tüm yapılarda anlamlı farklılıklar ölçülmüştür. Bu farklılıkların sonuçlarının insan kaynakları müdürleri tarafından örgütlerin yapılanmasına katkılarının olacağı da vurgulanmaktadır. Kendilerinden önceki nesille karşılaştırıldığında, Z neslinin iş tatmini, algılanan istihdam edilebilme vaadı, örgütsel tabiyet davranışı, algılanan iş güvenliği gibi algılarda daha düşük oranda sonuçlar verdiği bulgularda ortaya çıkmıştır. Son neslin ise çalıştığı kurumlara bağlılığının bir önceki nesilden daha düşük, işten ayrılma eğilimi ve iş değiştirme gibi konularda ise daha yüksek olduğu ve örgütsel ve yönetimsel desteğin hakir görüldüğü bulgularına varılmıştır. Anahtar Kelimeler: Z Nesli, Y Nesli, İşle ilgili davranışlar, turizm endüstrisi, İKM
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2014. Supervisor: Prof. Dr. Hasan Kılıç.
Keywords: Tourism and Hospitality Industry - Workers - Work Attitudes - Cyprus, North; Employee Motivation; Job satisfaction - Employee morale - Attitude (Psychology); Generation Z; Generation Y; Generational Differences; Work related Attitude; Tourism Industry; HRM; Tourism